Perancangan UI/UX Aplikasi Reminder Minum Obat Bagi Pasien TB Menggunakan Metode Design Thinking - Eka Novita Sari; Alfin Hidayat; Arum Andary Ratri; Nur Anis Agustina (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2026)
Tuberculosis (TB) remains a major public health problem in Indonesia, particularly due to low patient adherence to long-term therapy. This study aims to design a user interface (UI/UX) for a TB medication reminder application based on the Design Thinking method, emphasizing the involvement of family members as Medication Supervisors (PMO). The design process consists of the empathize, define, ideate, prototype, and test stages. Data were collected through interviews and observations involving patient families and healthcare workers, and analyzed using descriptive-qualitative methods. The application prototype was evaluated via usability testing to assess ease of use, effectiveness, and task completion success rates. The results indicate that the developed application increases patient adherence, simplifies medication consumption records, and provides integrated reporting features according to user needs. The average task completion success rate in usability testing reached 85%. This study recommends continued optimization of features and navigation to further support sustainable TB therapy outcomes.